Palliative care of patients with Parkinson's disease - Aranđelović, Branimirka; Simić, Svetlana; Bogdanović Vasić, Slobodanka; Mikić, Milena; Uzelac, Jovana; Glamočak, Sandra (PONS - medicinski časopis, 2024)
Parkinson's disease is a chronic, progressive, neurodegenerative disease that most often affects elderly people. The disease is characterized by a wide range of motor and non-motor symptoms, which, as the disease progresses, lead to significant disability, dependence on other people, and impaired quality of life. Currently, there is no medicine that can cure or stop the progression of the disease. With palliative care with a holistic approach and the involvement of a multidisciplinary team, most symptoms can be kept under control and provide support to caregivers, which significantly contributes to a better quality of life for both patients and their families, i.e., caregivers.
Keywords: palliative care; Parkinson’s disease; signs and symptoms; multidisciplinary team